Pengembangan E-Book Berbasis Flipbook Maker Tema Lingkungan Sahabat Kita Subtema Perubahan Lingkungan - Ai’nun Dalilah; Sukmanasa, Elly; Sundari, Fitri Siti (STKIP Andi Matappa Pangkep, 2022)
This study aims to determine the development of an e-book based on the environmental theme of our friend, the sub-theme of environmental change to be developed for fifth-grade students at the State Elementary School of Kebon Pedes 5, Bogor City, and to determine the feasibility of an e-book based on flipbook maker for the learning process carried out in school. The research method used in this study is the research and development method using the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation), but in this study, only the development stage is only to determine the development of teaching materials. Flipbook maker based e-book. The results showed that the electronic book based on the flipbook maker, the environmental theme of our friend, and the sub-theme of environmental change, was declared suitable for use based on validation by material experts persentase 91%, linguists with persentase 100%, and media experts persentase 92% as well as students as user responses with persentase 90,68% because it could increase students' enthusiasm for learning in class.